Effect of the carbonization and activation processes on the adsorption capacity of rice husk activated carbon - Ma, Hoa Thai; Ho, Van Thi Thanh; Pham, Nguyen Bao; Nguyen, Dat Chi; Vo, Kieu Thi Diem; Ly, Hung Cam; Phan, Tuan Dinh (Vietnam Journal of Science and Technology, 2017)
In this study, rice husk was used as a precursor to prepare activated carbon using steam as a physical activation agent. Steam for activation can be used to activate almost all raw materials. A variety of methods have been developed but all of these share the same basic principle of initial carbonization followed by an activation step with steam. The study also investigates the effects of preparation parameters on the surface characteristics of the carbon. These parameters include the range of temperature and time in the carbonization and activation. The initial carbonization, done at temperatures up to 500°C in 60 min, is a highly exothermic process where the temperature is strictly controlled. The creation of the internal surface is done during the activation step with steam at temperatures 800°C in 30 min., for which the BET surface area is up to 710.8m2/g. Besides, the iodine and methylene blue adsorption capacity of rice-husk carbon are the best that reach 865.98±6.5 and 217.86±1.0 (mg/g), respectively. The entire synthetic procedure was simple, environmental-friendly and economical-effectively. The application prospect of the activated carbon prepared in this work was much more promising due to its high adsorptive capacity.